2009
DOI: 10.1016/j.juro.2009.02.117
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser Ablation of the Prostate Versus Photoselective Vaporization of Prostate 60 cc or Less: Short-Term Results of a Prospective Randomized Trial

Abstract: Holmium laser ablation and photoselective vaporization of the prostate are safe and effective in patients with benign prostatic hyperplasia with a small to moderate size prostate. Both procedures are easy to learn but holmium laser ablation of the prostate requires a longer operating time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The blood transfusion rate was 14.2% in patients on warfarin and 14.7% in those on LMWHs. HoLAP is effective in smaller prostates, 92 with reduced transfusion rates. 93 Potassium-titanyl-phosphate (KTP) and lithium triborate lasers are used for photovaporization of the prostate (PVP), which is associated with an especially low rate of bleeding; a 0% transfusion rate has been reported in studies that include patients on anticoagulants.…”
Section: Laser Technologymentioning
confidence: 98%
“…The blood transfusion rate was 14.2% in patients on warfarin and 14.7% in those on LMWHs. HoLAP is effective in smaller prostates, 92 with reduced transfusion rates. 93 Potassium-titanyl-phosphate (KTP) and lithium triborate lasers are used for photovaporization of the prostate (PVP), which is associated with an especially low rate of bleeding; a 0% transfusion rate has been reported in studies that include patients on anticoagulants.…”
Section: Laser Technologymentioning
confidence: 98%
“…Reoperation rates at 1 year were 3.5% and 1.9% for the HoLAP and PVP groups, respectively. Bladder neck contracture (BNC) rates of 3.5% and 7.7% for the HoLAP and PVP groups, respectively, were noted and attributed to the authors' early phase of the learning curve and smaller size of the glands being treated [8].…”
Section: Holmium Laser Ablation Of the Prostatementioning
confidence: 98%
“…A recent 2009 study by Elzayat et al [8] compared HoLAP (80 W system) to PVP (80 W system) for the treatment of glands 60 cc or smaller. They reported a statistically significant increased operative time for HoLAP (69.8 min) as compared to PVP (55.5 min).…”
Section: Holmium Laser Ablation Of the Prostatementioning
confidence: 99%
“…In men with pros-tate sizes greater than 80 mL, Kumar [10] published data showing HoLAP to be efficacious and feasible with a mean lasing time of 77 minutes. In a comparative trial of HoLAP versus photoselective vaporization of the prostate (PVP), Elzayat et al [11] reported in a prospective randomized tri-al of 109 men that HoLAP required more operative time (70 minutes vs. 56 minutes).…”
Section: Holmium Laser Ablation Of the Prostatementioning
confidence: 99%